On the way to creating Ukrainian national cloud of open science - Svistunov, S.Ya.; Perkonos, P.I.; Subotin, S.V.; Tverdochlib, Ya.M. (Інститут програмних систем НАН України, 2021)
Modern conditions of science development, which are characterized by a significant increase in the volume of information, require new approaches to computational methods and new approaches to information processing. The article considers approaches to creating conditions and tools based on cloud technologies for more effective cooperation of research teams working on similar scientific problems.The article analyzes the stages of development of the European Open Science Cloud and presents the strategy of building the National Open Science Cloud. The article presents the main results of the development of a common information resource for scientific researches at the National Academy of Sciences of Ukraine, which can be considered as a prototype of the National Open Science Cloud, which integrates into the European Open Science Cloud.Prombles in programming 2021; 3: 27-39